'Orphans of Poetry': The poetry of childhood and the poetry for children of Robert Graves. Issue 1 (1st December 2016) - Joseph, Michael
'Orphans of Poetry' examines poems by Robert Graves in order to argue three related points: that Graves's ideas about childhood and children's poetry, which anticipate more contemporary attitudes, were significantly shaped by his harrowing experience in the trenches in World War I; that Graves had an extraordinarily complex idea of nonsense as something larger than reasonableness and believed in its 'explanatory power', a belief arising from a philosophical scepticism he adopted when he was in his early twenties; that his idea of nonsense dovetailed with the notion of poetic truth, or a kind of knowledge accessible only through poetry or only to readers of any age who had the capacity to conceptualize in the mode of a poet.